ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL MODERASI - Kristantri, Tisyri Manuella; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2012)
This research is aimed to examthe effect of firm’s size and debt to equity ratio to profitability which is moderated by earning’s growth on property and real estate firm’s listed at Indonesian Stock Exchange in 2009-2011. The technique of this analysis is Moderated Regression Analysis (MRA), which used 84 samples from secondary data with purposive sampling method. The result of this research showed that variables which are having a significant impact to profitability are debt to equity ratio and moderation of earning’s growth to debt to equity ratio. Keywords: debt to equity ratio, earning’s growth, firm’s size, profitability (ROE)